(untitled) (Eurasian Research Bulletin, 2023)
This article provides a comparative analysis of privacy laws from different regions, examining global approaches to protecting personal information. The analysis focuses on key regions, including the European Union, the United States, the Asia-Pacific region, Canada, and Australia. The article explores the General Data Protection Regulation (GDPR) in the EU, highlighting its influence and emphasis on individual rights and organizational obligations. It discusses the patchwork of privacy laws in the United States and the rise of state-level regulations such as the California Consumer Privacy Act (CCPA) and California Privacy Rights Act (CPRA). The diverse approaches in the Asia-Pacific region, ranging from comprehensive frameworks to national security-focused laws, are also examined. The Canadian Personal Information Protection and Electronic Documents Act (PIPEDA) and Australia’s Privacy Act, along with the Notifiable Data Breaches scheme, are discussed as examples of balancing privacy rights and commercial interests. The article concludes by emphasizing the importance of ongoing development and harmonization of privacy laws in the face of evolving technology and global data flows. The findings highlight the need for international collaboration and the challenges of cross-border data transfers. The article provides insights into the materials and methods employed, ensuring a reliable analysis based on legal texts, research papers, industry reports, and reputable sources.